Effect of long-term liquid dairy manure application on activity and structure of bacteria and archaea in no-till soils depends on plant in development - da Costa Soares, Stallone; Vezzani, Fabiane Machado; Favaretto, Nerilde; Auler, André Carlos; da Silva Coelho, Irene; de Sousa Pires, Araceli; Cruz, Leonardo Magalhães; de Souza, Emanuel Maltempi; Barth, Gabriel (Environmental science and pollution research international, 2024)
This study aimed to evaluate the impact of long-term liquid dairy manure (LDM) application on the activity and structure of soil bacterial and archaea communities in two cropping seasons over 1 year of a no-till crop rotation system. The experiment was run in a sandy clay loam texture Oxisol, in Brazil, including LDM doses of 60, 120, and 180 m 3 ha −1 year −1 , installed in 2005. Soil sampling was conducted during spring 2018 and autumn 2019 at 0–10-cm depth. Microbial biomass carbon and nitrogen, 16S rRNA gene sequencing, microbial respiration and quotient were performed. Over the 14-year period, LDM application increased soil microbial community activity. Analysis of 16S rRNA gene sequencing revealed dominance by Proteobacteria, Acidobacteria, and Actinobacteria phyla (67% in spring and 70% in autumn). Genera Pirulla and Nitrososphaera showed enrichment at LDM doses of 120 and 180 m 3 ha −1 year −1 doses, respectively. During spring, following black oat cropping, shifts in the relative abundance of Bacteroidetes, Proteobacteria, Firmicutes, Gemmatimonadetes, Verrucomicrobia, Chloroflexi, Actinobacteria, and AD3 phyla were observed due to LDM application, correlating with soil chemical indicators such as pH, K, Ca, Mn, and Zn. Our findings indicate that plant development strongly influences microbial community composition, potentially outweighing the impact of LDM. Our findings indicate that the application of liquid dairy manure alters the soil bacterial activity and community; however, this effect depends on the developing plant.